Favorable outcome of SARS-COV-2 infection in a patient with pituitary insufficiency - Fux Otta, Carolina (2020)
Fil: Fux Otta, Carolina. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas; Argentina.